Reinventing Philanthropy : A Framework for More Effective Giving - Friedman, Eric, 1977- (Book collections on Project MUSE., 2013)
Several years ago, the author decided to donate a substantial percentage of his income to charity. As many people do when making a big decision, he researched the best path he should take to accomplish his goal. After speaking with foundations, consultants, and nonprofit staff members, he found that few could adequately respond to his basic questions: How should donors choose the causes they support? How can donors maximize the impact of their giving?. In this book, the author shares the answers he found when exploring the world of charitable giving. What he discovered will help readers combine their business acumen with their compassion, soul-searching, and self-awareness so they can become highly effective donors. While many donors choose to direct their giving based on personal interests and passions, the author reinvents the best practices in philanthropic giving and demonstrates how the selection of donation recipients can be based more on maximizing a donation's benefits to those in need. He also provides specific strategies for effective giving, including the best ways to identify high-performance nonprofit organizations and the most important criteria for selecting causes to support.